2018
DOI: 10.1371/journal.pone.0200656
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatic steatosis as assessed by controlled attenuation parameter (CAP) in subjects with metabolic risk factors in primary care. A population-based study

Abstract: BackgroundPrimary care is the ideal setting for early identification of patients with non-alcoholic fatty liver disease (NAFLD). NAFLD is a potentially progressive disease that may lead to cirrhosis and liver cancer but is frequently underrecognized because subjects at risk are often not evaluated. Controlled attenuation parameter (CAP) is a reliable method for non-invasive quantification of liver fat. It has the advantage of simultaneous measurement of liver stiffness (LS), an estimate of liver fibrosis. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 33 publications
1
20
0
9
Order By: Relevance
“…A control group of 80 subjects matched by age and sex without metabolic risk factors was also studied. CAP and LSM were assessed using TE and found that there was a good statistical correlation between liver transaminases and increased LSM, suggestive of liver fibrosis [25].…”
Section: Discussionmentioning
confidence: 99%
“…A control group of 80 subjects matched by age and sex without metabolic risk factors was also studied. CAP and LSM were assessed using TE and found that there was a good statistical correlation between liver transaminases and increased LSM, suggestive of liver fibrosis [25].…”
Section: Discussionmentioning
confidence: 99%
“…The uninfected cutoff values for fibrosis stage were: LSM<10 kPa, F0-F2; LSM �10 kPa, F3-F4 [33]. The cutoff values for steatosis grade were: CAP>248 dB/m, S1; CAP>268 dB/m, S2; CAP>280 dB/m, S3 [38,39]. VCTE provided a measure of liver stiffness (lower kPa values indicate a more elastic liver), a surrogate measure for fibrosis.…”
Section: Liver Fibrosis and Steatosis Measurementmentioning
confidence: 99%
“…Nonalcoholic fatty liver disease (NAFLD) is a significant public health problem that is concomitantly increasing along with the high prevalence of obesity and diabetes . NAFLD represents the hepatic manifestation of metabolic syndrome, and it ranges from simple steatosis to nonalcoholic steatohepatitis (NASH) and cirrhosis .…”
Section: Introductionmentioning
confidence: 99%